A liposomal formulation for the oral application of the investigational hepatitis B drug Myrcludex B - Uhl, Philipp; Helm, Frieder; Hofhaus, Götz; Brings, Sebastian; Kaufman, Christina; Leotta, Karin; Urban, Severino; Haberkorn, Uwe; Mier, Walter; Fricker, Gert (European journal of pharmaceutics and biopharmaceutics, 2016)
The aim of this study was the development of a liposomal formulation containing specific tetraether lipids for the oral administration of the investigational hepatitis B peptide drug Myrcludex B. For this purpose, tetraether lipids were extracted from the extremophilic archaeon Sulfolobus acidocaldarius and purified in order to obtain the desired glycerylcaldityltetraether lipids (GCTE). Myrcludex B was synthesized by solid-phase synthesis and incorporated into liposomes containing 5mol% of GCTE. These liposomes showed a size, polydispersity index and zeta potential comparable to the standard liposomes. Cryo-EM micrographs of both liposomal formulations displayed low lamellarity, the prerequisite for high drug loading capacity. Long term storage of the GCTE-liposomes was achieved by freeze-drying using 100-500mM sucrose or trehalose as lyoprotectors. The lyophilized product showed high stability with a recovery rate of 82.7±1.6% of intact Myrcludex B observed after storage for 3months at −20°C as compared to a recovery rate of 83.3±1.3% directly after the freeze-drying process. In vivo, the GCTE-liposomal formulation led to substantial enhancement of the liver uptake of iodine-131-labeled Myrcludex B in Wistar rats. 3h after oral application, approximately 7% of the initial dose (corresponding to a 3.5-fold increase compared to the free peptide) could be detected in the liver. In summary, the GCTE-liposomes enabled efficient oral administration of Myrcludex B and provided long term storage by freeze-drying.